Fórmula integral para caracterizar hipersuperfícies em uma esfera unitária - Milfont, Thadeu Ribeiro Benicio (2010)
In this work, We consider compact rotational hypersurfaces M^n in the unit sphere S^(n+1)(1), obtaining some integral formulas and then applying these integral formulas to characterize the torus S^1(root(k/n))×S^(n−1)(root((n − k)/n)).